Insect immunology - Beckage, Nancy E. (Elsevier, 2008)
Given the critical importance of insect immunology in insect vector-parasite interactions and vector control, biological control of agricultural insect pests, and other key areas of entomological research and practice, a new comprehensive work summarizing recent breakthroughs in this rapidly expanding field is sorely needed. This work will constitute the first book-length publication on the topic of insect immunology since 1991, complimenting earlier works by offering a fresh perspective on current research. Interactions of host immune systems with both parasites and pathogens will be presented as well as the genomics and proteomics approaches which have been lacking in other publication